PENGUATAN KEPEMIMPINAN KEPALA SEKOLAH DALAM LINGKUP INTRA DAN EKSTRA SEKOLAH - Tri Nurwati (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2015)
The objective of this study is to describe strategies in selecting school principal as school community figure and model.  This study uses library analysis and observation to collect data. The observation took place on January to March 2015 at SMKN 8 Purworejo, Central Java.  Focus Group Discussion was also used complimentary to observation as well as seminar involving Association of Principal of SMK (MKKS SMK) in Purworejo County.  This study reveals six steps to identify such the principal: (1) to increase principal competenecy, (2) to increase capacity of human resources management, (3) to increase strategies to motivate teachers and students, (4) to increase leadership capacity, (5) to increase networking with DUDI, and (6) to increase development of school productivities.